Utilization of Mustard Seed Meal Extract for Improving Soil Health in a Small-Scale Organic Potato Cropping System. Issue 3 (4th February 2023) - Temmen, Daniel; Randall, John; Popova, Inna
ABSTRACT: Maintaining and improving soil health is one of the top priorities in organic agriculture to ensure crop production sustainability. Mustard seed meal extracts are promising organic soil amendments that can reduce pesticide pressure and improve crop yields. In this study, we investigated the potential of mustard seed meal extract developed in our laboratory, to improve soil health in organic potato systems. Field trials were conducted on two certified organic farms in Northern Idaho to 1) assess the changes in soil chemical indicators after mustard seed meal extract application; 2) evaluate the effect of mustard seed meal extract on microbial biomass carbon; and 3) measure plant-available nutrients levels in soil after mustard seed meal extract application. To the best of our knowledge, this is the first report studying the effect of mustard seed meal extract on soil quality in organic potato systems. Out of 27 soil chemical and biological indicators measured, 19 indicators were sensitive to the addition of mustard seed meal extract. The data obtained for organic and inorganic soil constituents indicate a positive impact of mustard seed meal extract on soil quality. Addition of mustard seed meal extract to soil increases Haney soil health score up to 1.5 times demonstrating the benefit of application for improving soil quality in organic production.